Kajian Kualitas Air, Potensi Karang Dan Ikan Karang Untuk Pengembangan Wisata Selam Di Desa Bondalem, Buleleng, Bali - Evrina Cahyani Sinaga; I Wayan Restu; Rani Ekawaty (Current Trends in Aquatic Science, 2020)
Abstract Bondalem Village is located in Tejakula District, Buleleng Regency, north of the Island of the Gods. This village is directly adjacent to the Bali Sea in the north, this condition makes tourism can develop especially diving tourism and activity. This purpose of this study is to examine the suitability of water quality in order to support the development plan of diving tourism in the waters of Bondalem Village, Tejakula District, Buleleng Regency. Data colection is carried out every once a month within 3 months in November, December 2018 and March 2019. This study uses the method of field observation and secondary data from the results of the literature study. In this study the method of data collection was done by direct measurement in the field for observations of the environmental conditions at the study site. The results of data collection in the form of data that supports the acquisition of environmental parameter data in regional and physical environmental suitability assessment. This study was carried out by analyzing the suitability of diving tourism, coral identification was assessed using the LIT (Line Intercept Transect) method while the abundance of reef fish species was studied using the UVC (Underwater Visual Census) method. Analysis of the data used is an analysis of the potential of coral reefs and land suitability. Determination of the level of land suitability as a diving tourism area using regional suitability matrix analysis considering ecological parameters and water quality. The live coral community cover in Bondalem waters ranges from 65.93% to 81.33% with a variety of reef fish species ranging from 16 families. Travel suitability index diving category is included in the very appropriate category (S1).